2015
DOI: 10.1590/1807-1929/agriambi.v19n4p324-329
|View full text |Cite
|
Sign up to set email alerts
|

Soro ácido de leite como fonte de nutrientes para o milho

Abstract: Realizou-se este estudo com o objetivo de avaliar o efeito do soro ácido de leite em atributos químicos do solo, na produção de matéria seca e no acúmulo de nutrientes na parte aérea de milho. O experimento foi conduzido em vasos, em casa de vegetação, entre fevereiro e maio de 2012, e o delineamento experimental utilizado foi em blocos ao acaso, em esquema fatorial 5 x 2, com quatro repetições. Os tratamentos consistiram na combinação de cinco doses de soro ácido de leite equivalentes a 0, 50, 100, 150 e 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
1
5
1
1
Order By: Relevance
“…Dias, Silva and Maia (2010) observed in their research that the treatments showed different behaviors, although with significant results only for the nitrogen effect with 105 kg ha -1 applied in isolation, at the beginning of tillering and in floral differentiation, and interactions with doses of NP, NK, PK, and NPK did not influence productivity. Mantovani et al (2015) found that serum doses of 200 m 3 ha -1 were not sufficient to increase the nutritional requirement of corn, which corroborates part of our results, since the highest dose of serum applied in this study was less than that cited by these authors. The authors also point out that this dose of the residue caused limitations in the growth of the crop, not meeting the nutritional needs of corn.…”
Section: -----------------------Mg Dm -3 ----------------------------------------Dag Kg -1 ------------supporting
confidence: 90%
See 1 more Smart Citation
“…Dias, Silva and Maia (2010) observed in their research that the treatments showed different behaviors, although with significant results only for the nitrogen effect with 105 kg ha -1 applied in isolation, at the beginning of tillering and in floral differentiation, and interactions with doses of NP, NK, PK, and NPK did not influence productivity. Mantovani et al (2015) found that serum doses of 200 m 3 ha -1 were not sufficient to increase the nutritional requirement of corn, which corroborates part of our results, since the highest dose of serum applied in this study was less than that cited by these authors. The authors also point out that this dose of the residue caused limitations in the growth of the crop, not meeting the nutritional needs of corn.…”
Section: -----------------------Mg Dm -3 ----------------------------------------Dag Kg -1 ------------supporting
confidence: 90%
“…Some authors are already studying the technical feasibility of using acid milk serum in agriculture, given the ability to supply nutrients. Mantovani et al (2015) concluded that the supply of acid milk serum increases the levels of available P and K, increasing the dry matter production of corn plants. It is worth mentioning that doses up to 200 m 3 ha -1 should be used in association with mineral fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…These results are different from the ones observed for the species Eugenia involucrata, which presented damaged development for all dosages evaluated. These results are also different from the ones found by Gheri, Ferreira and Cruz (2003), who, after application of acid whey on Panicum maximum, found increase in the production of dry matter, achieving higher production after application of 390 m³/ha of whey; by Schuster (2008), who tested daily irrigation of 200 mL and 400 mL in eucalyptus seedlings, the author observed an increase in height and collar diameter with application of a higher dosage; and by Mantovani et al (2015), who evaluated the whey potential as source of nutrients for maize and observed that the acid whey on the soil increases the production of maize plants dry matter and the accumulations of N, P, K, and Ca in the aerial part, if used whey in values superior to 200 m³ ha -1 . Figure 8 -Evaluation of indicators for aerial part dry matter weight (APDMW) (A), root dry matter weight (RDMW) (B), total dry matter (TDMW) (C), and development quality rate (DQR) for the species Inga vera Willd submitted to different fertigations.…”
Section: Inga Vera Willdcontrasting
confidence: 62%
“…As discussões ambientais do soro do leite evoluíram, no entanto, a essência continua intimamente relacionada com sua composição nutricional, que consiste de 93 a 94% de água, 4,4 a 5,0% de lactose, 0,7 a 0,9% de proteínas solúveis e 0,6 a 1,0% de sais minerais (MANTOVANI et al, 2015), índices que variam de acordo com o seu tipo (soro doce ou soro ácido), o ingrediente usado para a coagulação, a forma de armazenamento e processamento do leite, além das condições do animal pelo qual o leite foi retirado (RAD; LEWIS, 2014).…”
Section: Implicações Ambientais Do Soro Do Leiteunclassified